Análisis del impacto de la profesionalización de la secretaria ejecutiva gerencial graduada en la universidad técnica de Cotopaxi en el área secretarial de las empresas públicas y privadas del cantón Latacunga - Carrillo Puco, Mónica Gabriela (2015)
The present research work referred to analysis of the impact that the Executive Management Secretary graduated from the Technical University of Cotopaxi causes with the objective to identify and give efficient solutions to the lack of knowledge and skills to develop their activities. The work done in the first stage was developed based on the need that the Executive Secretaries have about the updating of knowledge at the moment of act in the workplace; the research was focused in topics such as: Public and Private companies, Information management, Executive Management Secretary and its professionalization....